HEALTHY LIFESTYLE IN LITHUANIA AND LATVIA STUDENT POPULATION IN THE CONTEXT OF INDIVIDUAL VALUES - Kinderis, Remigijus; Danielienė, Jūratė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
It is believed that the greatest impact on health is done by lifestyle, which is perceived as the habits and customs as the whole, exposed and amplified by socialization process during all human life. The research problem is formulated under the following main question: How healthy lifestyle is expressed when studying at a higher education institution? The aim of the research - to reveal the healthy lifestyle expression of students in tourism and recreation study programmes in the context of individual values. Research methodological substantiation: quantitative and qualitative research accessibility. Methods: individual expert interview (with higher school representatives) and anonymous questionnaire (students). It was established that: the main determinants of a healthy lifestyle are qualities of character, lifestyle, social environment, motivation, knowledge, communication with parents, other family members and surrounding people; the student’s choice of lifestyle is mostly determined by family and friends, in other words, those who surround them constantly; health value cherished in the family encourages students at least partially to live according to the principles of a healthy lifestyle. Also, lack of motivation, time and finances leads to and the indifference of the respondents to live according to the principles of a healthy lifestyle.